Pengaruh Latihan Senam Kardio dan High-Intensyty Interval Training Berbasis Penanganan Pandemik Corona Virus-19 Terhadap Vo2max Pada Siswa SSB Syekh Yusuf Gowa - Irfan Irfan; Ihsan Abbas (Seminar Nasional LP2M UNM, 2021)
Abstract. The purpose of this study was to determine the differences in the effect of cardio exercise and High-Intensity interval training on VO2max in students Syekh Yusuf Gowa. This research used the method eksperiment with 40 samples. Data is obtained by carrying out tests and measurements. Data were analyzed by inferential statistics t test.The results of hypothesis testing show: (1) there is an influence in the kardio exercise based on the handling of corona virus-19 on VO2max at Student SSB Syekh Yusuf Gowa. (2) there is the influence of the High-Intensity interval training based on the handling of corona virus-19 on VO2max at student SSB Syekh Yusuf Gowa. (3) there is the influence of the kardio exercise and than the High-Intensity interval training based on better handling of the corona virus-19 pandemic on VO2max in student SSB Syekh Yusuf Gowa.Keywords : Cardio Exercises, High-Intensity interval training, VO2Max